The buildings gallery: visualizing buildings - Bekker, Bram; Solleveld, Maarten (Journal of mathematics and the arts, 2022)
Buildings are beautiful mathematical objects tying a variety of subjects in algebra and geometry together in a very direct sense. They form a natural bridge to visualizing more complex principles in group theory. As such, they provide an opportunity to talk about the inner workings of mathematics to a broader audience, but the visualizations could also serve as a didactic tool in teaching group and building theory, and we believe they can even inspire future research. We present an algorithmic method to visualize these geometric objects. The main accomplishment is the use of existing theory to produce three-dimensional, interactive models of buildings associated with groups with a BN-pair. The final product, an interactive web application called The Buildings Gallery, can be found at https://buildings.gallery/ [Bekker, B. (2021, June). The Buildings Gallery].